(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
In the past pharmacovigilance happened 174 years back. In 1848, a little girl (Hannah Greener) died due to chloroform anesthetic before the elimination of an infected toenail. The reason for death was investigated, probably girl died of a lethal arrhythmia or pulmonary aspiration. There were 107 deaths occurred in the USA in 1937, for the reason that of the use of sulfanilamide elixir formulation prepared with the solvent used as a diethyl glycol. In 1938, In 1961, happened the thalidomide disaster. Dr. McBride investigated this disaster; he investigated that the 1.5% incidence of congenital malformations in babies had greater than before up to 20% in women who had taken thalidomide medicine for medical treatment during pregnancy. The WHO Programme for International Drug Monitoring (PIDM) was launched by WHO in 1968, after the thalidomide disaster major changed the system of pharmacovigilance globally, necessary to establish national systems for spontaneous ADR monitoring and reporting after consumer use. To conduct a retrospective observational study of adverse drug reactions for inpatient and outpatient in the different clinical departments in a tertiary care hospital. In the present study, a total of 749 adverse drug reaction reporting forms were reported out of which 990 ADRs occurred in 749 patients (inpatients n=502,67.02% and outpatients n=247,32.97%). The overall incidence of ADR was found0.0194%. At least one ADR was recorded in 0.25% of the admitted patients (IPD) and in 0.0067% of the outdoor patients (OPD). In this study male to female ratio was (60.0%) & (40.0%). A total of (82.62%) of ADRs were found nonserious as compared to serious (17.37%). The majority of the ADRs were reported as gastrointestinal system disorders, type-A (60.40%), probable (86.0%), mild (52.72%), preventable (definitely 67.87% and probably 24.24%). Predisposing factors were associated with age (24.14%), polypharmacy (68.38%), and multiple and intercurrent diseases (15.75%). The studies concluded that most adverse drug reactions involved gastrointestinal system disorders and are mild, preventable, and have a probable causality relationship with the suspected drug. ADR monitoring systems monitor unlisted ADRs and other drug-associated problems that have not been recorded during a clinical trial and prior to regulatory authorities to identify signals of new and suspected unexpected unknown ADRs.